Integrating livestock in CAADP framework: Policy analysis using a dynamic computable general equilibrium model for Ethiopia - Gelan, Ayele; Engida, Ermias; Caria, A. Stefano; Karugia, Joseph T. (International Livestock Research Institute, 2011)
Researchers and policymakers increasingly recognize that the livestock sector supports the livelihoods of a large proportion of rural households in most African countries and may play an important role in rural poverty reduction strategies. To develop this insight, economy-wide models should capture both the biological, dynamic relationships between the stocks and flows of livestock and economic linkages between this sector and the rest of the economy. This study extends an existing dynamic recursive general equilibrium model for the Ethiopian economy so as to better model the livestock sector. A separate herd dynamics module enables researchers to specify stock-flow relationship, distinguishing between the capital role of livestock and the flow of livestock products. The authors also improved the underlying system of economic accounts to better capture draft power and breeding stocks. They used this model to simulate separate, realistic Total Factor Productivity (TFP) shocks to three agricultural subsectors—cereals, cash crops, and livestock—and compared them to a baseline scenario replicating the 1998–2007 productivity trends, following Dorosh and Thurlow (2009), who examined CAADP productivity scenarios. The results revealed the important role of the livestock sector in increasing various measures of GDP and combating food insecurity. Agricultural GDP and overall GDP growth levels achieved in the livestock TFP shock scenario are very similar to those achieved in the cereal TFP shock scenario, contrary to previous assumptions. Importantly, as factors are dynamically re-allocated between agricultural activities, our analysis highlighted the inefficiency of strategies focusing on cereal sector development alone. Moreover, livestock sector productivity growth led to greater factor income growth, particularly labor income, than in the other simulations. Labor is the predominant asset of poor household; hence, a livestock-led scenario realizes large gains in income and food consumption growth.